A modified Kakwani measure for health inequality - Mototsugu Fjugushige; Noriko Ishikawa; Satoko Maekawa (Health Economics Review, 2012)
We propose simple modifications for the Kakwani tax progressivity measure that make it suitable for evaluating access inequality for medical services. Our modification is to measure inequality using the ratio of the concentration index to the Gini coefficient instead of the difference between them. We also propose a measure using the Gini coefficient or concentration index of consumption expenditure as the denominator in the modified measure as an alternative type of modified measure. This measure can also be interpreted as the income/consumption expenditure elasticity evaluated at the mean. Additionally, we propose a decomposition method using expenditure components and provide an empirical example with Japanese data.
Keywords: I14; I10; 330; health inequality; Kakwani measure; decomposition; Gesundheitsversorgung; Soziale Ungleichheit; Indexberechnung; Steuerprogression; Gini-Koeffizient; Dekompositionsverfahren; Japan